Exploratory study for the electrochemical mining of magnesium in marine brines of Abangares - Brenes-Granados, Monserrat (2025)
In the Colorado de Abangares district of Guanacaste, Costa Rica, there is significant salt production, much of which is carried out by sun drying. In addition to the main product, sodium chloride, other by-products can be extracted from the concentrated brines by electrochemical precipitation. To explore this option, brine samples are taken from several local salt mines. These brines have very high salinity values ​​between (100-340) PSU and basic pH values ​​between (8-15). They are rich in magnesium, poor in calcium, and have a lithium content too low to be commercially exploitable. The main product of electrochemical precipitation of the brines is magnesium hydroxide Mg(OH)2, with an estimated production cost of about USD 0.036 per gram for the electrolysis proposed in this study.